The Porifera microeukaryome: Addressing the neglected associations between sponges and protists - Nascimento-Silva, Gabriel; Hardoim, Cristiane Cassiolato Pires [UNESP]; Custódio, Márcio Reis (Elsevier, 2022)
While bacterial and archaeal communities of sponges are intensively studied, given their importance to the animal's physiology as well as sources of several new bioactive molecules, the potential and roles of associated protists remain poorly known. Historically, culture-dependent approaches dominated the investigations of sponge-protist interactions. With the advances in omics techniques, these associations could be visualized at other equally important scales. Of the few existing studies, there is a strong tendency to focus on interactions with photosynthesizing taxa such as dinoflagellates and diatoms, with fewer works dissecting the interactions with other less common groups. In addition, there are bottlenecks and inherent biases in using primer pairs and bioinformatics approaches in the most commonly used metabarcoding studies. Thus, this review addresses the issues underlying this association, using the term “microeukaryome” to refer exclusively to protists associated with an animal host. We aim to highlight the diversity and community composition of protists associated with sponges and place them on the same level as other microorganisms already well studied in this context. Among other shortcomings, it could be observed that the biotechnological potential of the microeukaryome is still largely unexplored, possibly being a valuable source of new pharmacological compounds, enzymes and metabolic processes.
Keywords: Culture-dependent approaches; Culture-independent approaches; Eukaryotic microorganisms; Holobiome; Molecular pitfalls